AVENGERS : X-SANCTION - Loeb, Jeph; McGuinness, Ed; Vines, Dexter; Hollowell, Morry; Deschesne, Albert (New York, NY : MARVEL WORLDWIDE, INC., 2012)
Cable sacrificed himself to save his daughter Hope; now he's back with an impossible mission. In the space of 24 hours he has set his sights on destroying all the Avengers because they did not mangage to save Hope.
"Contains material originally published in magazine form as Avengers : x-sanction -4"
Keywords: Avengers (Fictitious characters) -- Comic books, strips, etc; Superheroes -- Comic books, strips, etc; Comic books, strips, etc. -- United State; Graphic novels